FAKTOR RISIKO KEMATIAN PRE DISCHARGE PADA NEONATUS YANG LAHIR DENGAN ASFIKSIA - , MASJUN; , dr. Madarina Julia, Sp.A(K), MPH, PhD ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: According to the WHO, of 4-9 million newborns with asphyxia, around 1.2 million babies die each year. It is estimated that approximately 23 % of all newborn deaths are caused by asphyxia and most of the babies die at birth. Some conditions that can affect newborns to suffer asphyxia are gestational age, mode of delivery, birth weight, history of seizures, infection and hypoglycemia. In Cilacap Local Hospital in 2012 infant mortality reaches 105 deaths. Asphyxia is a leading cause of death some 42 deaths Objective: This study aimed to determine the risk factors for pre-discharge mortality due to asphyxia and to determine newborn conditions, gestational age, mode of delivery, low birth weight, history of seizures, hypoglycemia, and infection diseases. Methods: This was observational with a case-control study design. The population was all neonatal in Perinatology Room of Cilacap Local Hospital. The samples were neonatal with Apgar score of less than 7 or those who received positive pressure ventilation. Univariate data analysis was performed descriptively to show the proportion, bivariable data analysis used Chi-square, and multivariable data analysis was by multiple logistic regressions. Results: Severe asphyxia increases the risk of pre-discharge mortality at 1, 82 times, gestational age <37 or> 42 weeks increased the risk of pre-discharge mortality at 4.9 times, mode of delivery with the SC increases the risk of predischarge mortality 4.25 times, low birth weight increases the risk of predischarge mortality was 3.26 and seizures increase the risk of pre-discharge mortality by 2.56 times. Conclusion: Severe asphyxia was likely to be at risk of causing pre-discharge mortality compared with moderate asphyxia. Gestational age less than 37 weeks or over 42 weeks, the mode of delivery with the SC, low birth weight and seizures were the risk factors for pre-discharge mortality in patients born with asphyxia.